The Management of Urticaria Pigmentosa: A Literature Review - Pujiastuti, Agustina Tri (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
ABSTRACT Background: Urticaria pigmentosum is the most common skin manifestation of cutaneous mastocytosis. This disease has similarity with others, therefor misdiagnose is common occurrence. Methods. Literature searching was conducted using databases such as PubMed, Google Scholar, and Web of Science using Search terms included